A single-phase full-visible-spectrum phosphor for white light-emitting diodes with ultra-high color rendering. Issue 48 (7th December 2020) - Zhang, Xiangting; Zhang, Dan; Zheng, Zhibo; Zheng, Baofeng; Song, Yanhua; Zheng, Keyan; Sheng, Ye; Shi, Zhan; Zou, Haifeng
Abstract : Through the regulation of energy transfer in the phosphor, a single-phase full-visible-spectrum YMAS:Eu 2+, Mn 2+ phosphor-converted WLED achieves an ultra-high Ra value. Abstract : Excellent luminous performance and high color rendering are the keys to white light-emitting diode (WLED) illumination. This work reports a single-phase full-visible-spectrum Y2 Mg2 Al2 Si2 O12 (YMAS):Eu 2+, Mn 2+ phosphor for WLEDs with ultra-high color rendering. The luminescence of a single Mn 2+ doped YMAS phosphor is very weak due to the spin-forbidden transition of Mn 2+, while it can be dramatically enhanced in the YMAS:Eu 2+, Mn 2+ system through efficient energy transfer from the sensitizer Eu 2+ . Meanwhile, the luminescent color of this phosphor can be tuned from cyan to cold white, to warm white, and finally close to the yellow region by controlling the activator concentration and energy transfer process. Its good thermal and chromaticity stability meet the requirements of application in WLEDs. Its stable photochromic performance at different excitation wavelengths (365–395 nm) indicates that it can be used in different ultraviolet chips. The YMAS:0.03Eu 2+, 0.30Mn 2+ phosphor-converted WLED achieves an ultra-high color rendering index (Ra = 93.3), near-standard chromaticity coordinates (CIE = (0.3343, 0.3388)) and a suitable correlated color temperature (CCT = 5417 K).